Pengolahan Bonggol dan Batang Pisang sebagai Strategi Pemberdayaan Ekonomi Mualaf (Studi Eksperimen melalui Pelatihan Pengolahan Nugget Bonggol Pisang dan Sambal Batang Pisang pada Mualaf di Desa Bulu Lor Kec. Jambon Ponorogo) - Anggraini, Yulia; Rahmawati, Yunaita (Proceedings of Annual Conference on Community Engagement, 2018)
A convert to Bulu Lor Village, Jambon Subdistrict, Ponorogo Regency comes from residents who previously embraced Buddhism and then converted to Islam. Buddhism developed in the village because it was spread through neat da’wah management and supported by sufficient funding and supported by the lack of mental and spiritual strength and economic material in some villages. Based on data from the Central Statistics Agency in 2018 the population of Bulu Lor Village is 4,000 people. Of these, 510 people rely on agriculture and farm laborers as economic livelihoods to fulfill their daily needs and 25 of them are converts. The convert group belongs to the marginal / mustad’afi> n / left behind in terms of economic welfare. Then it takes effort to improve the economic level of converts in order to strengthen faith in the Islamic religion so as not to return to Buddhism. Processed innovations from banana weevils to nuggets and sambal are alternative economic empowerment for converts, considering the easy-to-obtain materials, relatively easy processing methods, and the high potential of products accepted by the community if sold so that after training, converts are interested and continue to make nuggets and sambal from banana weevil as a superior product of Bulu Lor Village, which in turn has an impact on the economic growth of converts.